1997
DOI: 10.1029/96rg03194
|View full text |Cite
|
Sign up to set email alerts
|

High‐altitude energy source(s) for stable auroral red arcs

Abstract: Abstract. Stable auroral red (SAR) arcs have been viewed across the midlatitude night sky with interest since their discovery in 1956. This relatively late discovery (compared to the poleward aurora) is a direct consequence of the subvisual levels of the delicate and diffuse light that makes up the SAR arc. Except in rare instances when the emissions actually crossover the threshold to visible levels, optical instruments are required to register their presence and document their morphology and occurrence frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
179
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(193 citation statements)
references
References 83 publications
12
179
2
Order By: Relevance
“…They were reported as being observed in all directions, including the South, and to be red (Yau et al 1995) which makes them unfavorable candidates for classical aurorae. By their features these could have been stable auroral red (SAR) arcs (Zhang 1985) which in modern times are seen at mid-latitudes mainly during the recovery phase of geomagnetic storms (Kozyra et al 1997). These arcs are mainly driven by the ring current and differ from normal auroral phenomena.…”
Section: Comparison Of Aurorae During the Maunder And Dalton Minimamentioning
confidence: 99%
“…They were reported as being observed in all directions, including the South, and to be red (Yau et al 1995) which makes them unfavorable candidates for classical aurorae. By their features these could have been stable auroral red (SAR) arcs (Zhang 1985) which in modern times are seen at mid-latitudes mainly during the recovery phase of geomagnetic storms (Kozyra et al 1997). These arcs are mainly driven by the ring current and differ from normal auroral phenomena.…”
Section: Comparison Of Aurorae During the Maunder And Dalton Minimamentioning
confidence: 99%
“…Furthermore, the total energy, contained in the ring current particles, which is of the order of 1023 erg, is sufficiently large to cause appreciable atmosphere ionization or heating if released in a short time. Many effects, like subauroral electron temperature enhancements [Brace et al, 1967], stable auroral red arcs (SAR) [Kozyra et al, 1987[Kozyra et al, , 1997 and energetic neutral and ion precipitating fluxes [Dessler et al, 1961], are observed at midlatitudes as consequences of this energy release. Moreover, the ring current can also act as an energy source contributing to plasma instabilities and wave growth.…”
Section: Paper Number 1999ja900310mentioning
confidence: 99%
“…The upper atmosphere also provides evidence for a partial ring current during storms, with Craven et al (1982) (and references therein) showing that stable auroral red (SAR) arcs are primarily limited to the dusk-to-midnight sector. In their review of SAR arcs, Kozyra et al (1997a) concluded that the Coulomb interaction between the thermal electrons and the ring current is responsible for the magnetospheric heat flux that produces SAR arcs. From simulations, Liemohn et al (2000) showed that the local time asymmetry of the partial ring current matches the SAR arc observations.…”
Section: Introductionmentioning
confidence: 99%